Human Vs. Machine: Why Young Learners Need New Ways for Learning - Wishnoebroto, Wishnoebroto (Bina Nusantara University, 2010)
Learners in the 21st century face a new kind of challenge considering the presence of the new technology. Nowadays, they have more option to learn by using the new technology. Teachers, on the other hand, have to be aware of these instruments. Instead of looking at technology as a threat, teacher should understand their position as teacher while at the same time, coping and embracing the new technology. This article tries to illustrate the challenges considered by teachers and parents of the new learners.